Makna dalam Komunikasi Pembelajaran Online pada Mahasiswa selama Pandemi Covid-19 - Andreana; Dede Lilis Chaerowati (UNISBA Press, 2022)
Abstract: The use of the Internet has begun to be carried out in various fields and humanitarian activities, one of which is in the world of education, especially in higher education. Almost all universities in Indonesia use online media in lectures during the Covid-19 pandemic. The cancellation and implementation of teaching and learning activities in several universities was canceled due to the pandemic, this was considered the right decision to reduce contact and reduce mass crowds (Social and Phsycal Distancing) during the Covid-19 pandemic. There are several universities that have implemented online lectures before the pandemic, one example is the Bandung Islamic University (UNISBA). Unisba (Bandung Islamic University) is one of the private universities in Bandung which also organizes online lectures during the Covid-19 pandemic. Based on the regulations of the Minister of National Education and the regulations of the Ministry of Education and Culture, Unisba enforces the online lecture so that all students and lecturers as well as all employees at Unisba can avoid Covid-19. The communication that is carried out between lecturers and students during lectures has shifted from face-to-face lectures directly to the use of media as a tool to communicate with each other so that recovery continues as well as it should. The purpose of this study was to find out the motives, meanings and experiences of Fikom Unisba students in carrying out online lecture activities during the Covid-19 pandemic. This study uses a qualitative research technique with Alfred Schutz's Phenomenological approach to take a deeper look at students who carry out distance/online learning activities. Researchers carried out the data collection process by conducting observations and interviews in the field. The results of this study indicate that there are two motives analyzed, namely In order to motive for online lectures during the Covid-19 pandemic for Fikom Unisba students, namely the motive for health purposes, the motive for educational purposes, and the motive for technology purposes and Because of the motive for online lectures during the COVID-19 pandemic. 19 for Fikom Unisba students is the motive for the advantages and disadvantages of online lectures, the advantages of which are to facilitate learning activities, and the difficulty of capturing the material presented. Abstrak. Penggunaan internet mulai banyak dilakukan di berbagai bidang dan aktivitas kemanusiaan, salah satunya dalam dunia pendidikan, terutama di pendidikan tingkat tinggi. Hampir semua universitas di Indonesia menggunakan media online dalam perkuliahan selama pandemi Covid-19. Peniadaan dan pelaksanaan kegiatan belajar dan mengajar dalam beberapa universitas ditiadakan karena pandemi, hal ini dinilai menjadi keputusan yang tepat untuk mengurangi kontak dan mengurangi kerumunan massa (social and phsycal distancing) pada masa pademi Covid-19. Terdapat beberapa universitas yang sudah menerapkan perkuliahan online sebelum pandemi, salah satu contohnya adalah Universitas Islam Bandung (Unisba). Unisba (Universitas Islam Bandung) merupakan salah satu universitas swasta di Bandung yang juga menyelenggarakan perkuliahan daring/online selama masa pandemi Covid-19. Berdasarkan Peraturan Mendiknas dan Peraturan Kemendikbud, Unisba memberlakukan kuliah online tersebut agar seluruh mahasiswa dan dosen juga seluruh karyawan di Unisba dapat terhindar dari Covid-19. Komunikasi yang dilkakukan antara dosen dan mahasiswa pun di saat perkuliahan telah bergeser dari perkuliahan tatap muka secara langsung bergeser kepada penggunaan media sebagai alat untuk berkomunikasi satu sama lain agar perkulihan tetap berjalan dengan baik dan seharusnya. Tujuan dari penelitian ini adalah mengetahui motif, makna dan pengalaman mahasiswa Fikom Unisba dalam menjalankan kegiatan perkuliahan online selama pandemi Covid-19. Penelitian ini menggunakan teknik penelitian kualitatif dengan pendekatan Fenomenologi Alfred Schutz untuk melihat lebih dalam mengenai mahasiswa yang melakukan kegiatan pembelajaran jarak jauh/daring. Peneliti melakukan proses pengumpulan data dengan melakukan observasi dan wawancara di lapangan. Hasil penelitian ini menunjukkan terdapat dua motif yang dianalsis yaitu In order to motive perkuliahan online di masa pandemi Covid-19 pada mahasiswa Fikom Unisba adalah motif tujuan kesehatan, motif tujuan pendidikan, dan motif tujuan teknologi dan Because of motive perkuliahan online di masa pandemi Covid-19 pada mahasiswa Fikom Unisba adalah motif kelebihan dan kekurangan dari perkuliahan online kelebihannya mempermudah kegiatan belajar, kekurangannya kesulitan menangkap materi yang disampaikan.